STUDI PERENCANAAN PENATAAN KAWASAN ALUN-ALUN KOTA BREBES - Santoso, Eko Budi (Semarang State University, 2008)
The physical meaning of Brebes Square has decline todays. It is happen because the square elevation is almost same as the elevation of streets arround it, the increasing number of street hawkers and the less arrangement of utilities. For that reasons, the Brebes Square planning and arranging study is needed. The planning methods using continuation, togetherness, conflict minimalization and sustainability basic approachs. The programs are arrangement inside, including increase the elevation up to 75 cm from the streets arround it, create the water absorbtion and drainage, change the pedestrian ways, rearrangement the lamp nodes, increase the plants, arrangement the street hawkers, removing the main flag mast, relocation the statue, to mislay the gate, and increase the utilities. The arrangement outside including increase the elevation of pedestrian ways up to 25 cm from the streets arround it, increase the plants, change the pedestrian ways, increase the utilities and excuse from the advertisement board.Alun-alun Kota Brebes saat ini mengalami kemunduran makna fisiknya, disebabkan ketinggian alun-alun hampir sama dengan jalan disekelilingnya, banyaknya pedagang kaki lima dan kurang tertatanya sarana prasarana yang ada. Untuk itu diperlukan studi perencanaan penataan kawasan Alun-alun Kota Brebes. Metode perencanaan menggunakan pendekatan asas pelestarian, kebersamaan, minimalisasi konflik dan keberlanjutan. Program penataan kawasan alun-alun Kota Brebes meliputi penataan dalam alun-alun yang terdiri dari peninggikan alun-alun menjadi 75 cm dari jalan sekelilingnya, membuat resapan air dan drainase, mengganti trotoar, penataan kembali titik lampu, penambah tanaman, menata pedagang kaki lima, pemindahan tiang bendera utama, merelokasi patung, menghilangkan gerbang alun-alun dan menambah sarana prasarana; penataan luar alun-alun terdiri dari peninggian pedestrian menjadi 25 cm dari jalan sekelilingnya, menambah tanaman, mengganti trotoar, menambah sarana prasarana dan bebas dari papan reklame